2011
DOI: 10.7773/cm.v37i4b.1873
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of the recruitment of Peruvian anchovy (Engraulis ringens) between 1961 and 2009

Abstract: The principal objective of this work is to present a new model for the assessment of recruitment of the northern-central stock of Peruvian anchovy (Engraulis ringens), and use it to estimate monthly time series of recruits and pre-recruits between 1961 and 2009. The model is length-based and has monthly temporal resolution, allowing the variability in abundance and seasonality of recruitment to be modeled based on fishery and scientific survey information. The anchovy population is modeled with two recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Another, more direct, environmental cue for breeding seabirds could also be the onset of anchovy spawning that mainly occurs during the egg‐laying period. The timing of anchovy spawning likely forecast anchovy availability later in the in summer and fall when recruits integrate the stock (Oliveros‐Ramos and Peña ), at the period when most young seabirds become independent. These hypotheses offer exciting perspectives to test how environmental cues trigger determine seabird breeding onset, and to better understand the consequences of interannual variability in environmental conditions on seabird reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another, more direct, environmental cue for breeding seabirds could also be the onset of anchovy spawning that mainly occurs during the egg‐laying period. The timing of anchovy spawning likely forecast anchovy availability later in the in summer and fall when recruits integrate the stock (Oliveros‐Ramos and Peña ), at the period when most young seabirds become independent. These hypotheses offer exciting perspectives to test how environmental cues trigger determine seabird breeding onset, and to better understand the consequences of interannual variability in environmental conditions on seabird reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Anchovy biomass close to the coast was higher in summer than in winter (Appendix : Fig. F2a), most likely due to the arrival of new recruits (Oliveros‐Ramos and Peña ), and to the distribution of water masses. Indeed, anchovy horizontal habitat range is intimately linked to highly productive, cold coastal waters (Bertrand et al.…”
Section: Discussionmentioning
confidence: 99%
“…To represent fishing pressure, we used (as a covariate) the monthly landings of anchovy from industrial fisheries divided by the yearly quota. We built climatologies (monthly average over years) of the fishing pressure for the periods 1952−1968, 1977−1990 and 2000−2014. Data were available from articles already published for the periods 1952−1968and 1977(Tsukayama & Palomares 1987, Oliveros-Ramos & Peña 2011, and for the recent period they were provided by IMARPE (www. imarpe.…”
Section: Anchovy Data: Abundance and Catchesmentioning
confidence: 99%
“…In contrast, during 1970−1990, the warmer offshore Surface Subtropical Water approached closer to the coast, providing habitat favorable to sardine (Swartzman et al 2008). Moreover, the lack of seasonality in anchovy abundance during 1977−1990 may be related to the effects of recurrent El Niño events, which, combined with the low abundance of the adult stock and an intensive fishery, was not conducive to successful reproduction of anchovy (Jordan 1976, Oliveros-Ramos & Peña 2011.…”
Section: Cormorants Pelicans Boobiesmentioning
confidence: 99%
“…Engraulis spp. seem to share some life-history traits such as a very variable recruitment on both temporal and spatial scales (Borja et al, 2008;Cahuin et al, 2009;Cochrane et al, 1998;Oliveros-Ramos & Peña 2011;Peck et al, 2013;Shannon et al, 1996); a protracted reproductive season maintained by a batch-spawning strategy that produces multiple cohorts recruiting to the fisheries (Claramunt et al, 2012;Funamoto, 2002;McEvoy & McEvoy, 1992;Ribeiro et al, 1996;Richardson et al, 1998); a high natural mortality during their early life history, as is found in most teleost fishes with broadcast spawning (Anderson, 1988); a relatively fast growth rate with a short life span of 4-5 years and a maximum length ranging of 18-20 cm (Blaxter & Hunter, 1982).…”
Section: Introductionmentioning
confidence: 99%